Antibodies to SARS-CoV-2 in follicular fluids and their association with assisted reproduction - Chillon, Thilo Samson; Weiss, Gregor; Demircan, Kamil; Minich, Waldemar B.; Schenk, Michael; Schomburg, Lutz (Frontiers in Immunology, 2023)
Every second woman suffering from infertility asks for medical help. There is public concern that vaccination-induced antibodies (Ab) are negatively associated with fertility. A recent study has demonstrated an association between SARS-CoV-2 vaccination and a lower pregnancy rate in the subsequent 60 days. Consequently, Ab could affect fertility success in assisted reproduction. To address this question, we compared fertilization outcomes of vaccinated (n=35) and nonvaccinated (n=34) women. Paired serum samples and multiple follicular fluids (FF) (up to 10 from the same donor) were collected during the course of assisted reproduction and characterized for oocyte quality, the presence of Ab and trace element concentrations. The results showed a positive correlation of vaccination-induced neutralizing activity of SARS-CoV-2-Ab in serum and FF. On average, Ab concentrations in serum were higher than in the corresponding FF. However, wide variations in SARS-CoV-2 Ab titers were observed between different FF, correlating to trace element levels, even when retrieved from the same donor. Overall, FF contents are highly variable, but no negative association was observed between Ab in serum or FF and fertilization success and oocyte development, supporting the safety of SARS-CoV-2 vaccination during assisted reproduction.